Effect of eclampsia on pregnancy outcome at the tertiary care center - Yadava, Pushpa A.; Jani, Shashwat K.; Shyara, Ashish J.; Mehta, Shital T.; Solanki, Tejas V.; Desai, Forum A.; Mehta, Kush M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Eclampsia is a common medical and life-threatening emergency condition mainly seen in 5-10% of all pregnancies and that is a major cause of maternal and perinatal morbidity and mortality The aim of the study to find out the fetomaternal outcomes of eclampsia in tertiary care hospital and to analyse the trend of eclampsia and associated epidemiological variables. Methods: This retrospective analytical study was undertaken with 40 clinically diagnosed women with eclampsia in their third trimester of pregnancy in the Department of Obstetrics and Gynaecology, at tertiary care hospital from July 2020 to December 2021. Women who came to the hospital with eclampsia or developed eclampsia during hospital stay were included in our study. Results: In our study, the antepartum eclampsia was in 32 cases (80%), primigravida 27 cases (67.5%), maternal age (21-30 years) 26 cases (65%). Cesarean section was the mode of delivery in 26 cases (65%). NICU admission is required by 20 neonates (50%). Conclusions: Eclampsia is an important cause of maternal and perinatal morbidity and mortality. Providing quality antenatal health care services, increasing awareness of patients about warning symptoms, proper investigations, timely delivery, and proper monitoring in the intrapartum and postpartum period have the potential to improve maternal and perinatal outcomes.